Observations on fragrance collection behaviour of euglossine bees (Hymenoptera, Apidae) - Peter W.H. Holland (Revista Brasileira de Entomologia, 2015)
Male bees of the tribe Euglossini collect volatile chemicals secreted by orchids using dense patches of hair on the front tarsi. After collecting chemicals, the bee hovers while transferring these fragrances to invaginations on the hind tibiae. The fragrance collection and hovering behaviours are repeated multiple times. Here I report preliminary field observations on the length of fragrance collection and hovering phases in bees of the Eulaema meriana (Oliver, 1789) mimicry complex visiting the orchid Catasetum discolor in Kavanayén, Venezuela. I observed that in extended visits with many cycles of fragrance collection and hovering, the length of each collection phase gradually increased, while the length of hovering phase was static. This suggests either that chemicals secreted by orchids are in limited supply or that efficiency of fragrance collection drops. Keywords: Neotropical Orchid bees Sexual selection